Simulation of the variable assembly of MGT-SOFC systems to optimize the mechanical efficiency. Issue 1 (May 2021) - Dückershoff, R.; Berg, H.P.; Kleissl, M.; Himmelberg, A.
Abstract: Simulations of various modifications and technical solutions to improve the energy yield when connecting micro gas turbines and SOFC high-temperature fuel cell systems are presented. Above all, heat integration measures enable an increase in system efficiency and a reduction in primary energy input. On the basis of analysis of efficiencies and the heat output it is shown, which high influence the modifications for the improvement of the hybrid process have on the energy yield. Finally, an optimal configuration is worked out, which enables primary energy to be used with the highest possible efficiency. Particular emphasis is placed on the use of gaseous fuels from renewable energy sources. Preparation mechanisms, e.g., the reforming of used methane, and the improvement of the heat insulation materials was also taken into account. All in all, electrical total efficiencies for the optimized hybrid system of more than 65 % could be proven and additional thermal energy for heating purposes was extracted. Overall efficiency for the utilization of the energy content of the primary energy of up to 95 % was then achieved. Entire systems with a maximum system output of around 270kW were examined. In the near future, these plants can replace existing fossil-fuel power plants. Due to the achievable flexibility, the previous security of supply and load fluctuation compensation can also be performed.